An exploration of teaching reading practice and pedagogical knowledge in secondary schools - Alzahrani, Mohammed Abdullah; Almalki, Sami Mohammed (Frontiers in Education, 2025)
This study investigates the pedagogical strategies employed by Saudi secondary school English as a Foreign Language (EFL) teachers in the teaching of reading. It explores teachers' instructional practices and underlying perceptions of reading pedagogy using qualitative methods, including interviews and classroom observations. It focuses on identifying opportunities for enhancing both classroom teaching and professional development programmes. Findings from nine EFL teachers in the Southwest Saudi Arabia reveal a consensus on the importance of reading instruction, alongside significant variation in pedagogical knowledge and implementation. The analysis reveals several critical dimensions, including linguistic knowledge encompassing phonetics and morphology, diverse teaching methodologies, reading comprehension strategies, assessment techniques, and approaches to student motivation. Particularly evident is the need to develop students' reading comprehension, vocabulary acquisition, and fluency. The study shows that teachers place a strong emphasis on the foundational elements of literacy, such as phonology and reading fluency. Importantly, it reveals how effective pedagogical practices correlate with increased student engagement and satisfaction in reading activities. These findings have significant implications for the redesign of teacher training programmes and the development of more effective frameworks for teaching reading in EFL contexts.